Digital trophies: using social media to assess wildlife crime in Lebanon - André F. Raine; Jason Gregg; Lloyd Scott; Axel Hirschfeld; Ghassan Ramadan-Jaradi; Filippo Bamberghi (Oryx)
Illegal hunting of migratory birds across the Mediterranean region is a serious international conservation issue with population-level impacts. We analysed photographs posted on social media platforms to assess the bird species illegally targeted in Lebanon. During 2011–2023 we reviewed 1,844 photographs publicly posted by poachers on Facebook and Instagram. In these images we identified 212 bird species, of which 94% are legally protected. Many are species of conservation concern, with 19 listed as threatened or Near Threatened on the IUCN Red List and 33% experiencing population declines in Europe. The five bird species with the most individuals illegally killed were the barn swallow Hirundo rustica, blackcap Sylvia atricapilla, European bee-eater Merops apiaster, Eurasian golden oriole Oriolus oriolus and ortolan bunting Emberiza hortulana. Raptors and other large soaring birds were particularly prevalent, with 35 species of raptor (particularly the European honey-buzzard Pernis apivorus, Eurasian sparrowhawk Accipiter nisus, common kestrel Falco tinnunculus, short-toed snake-eagle Circaetus gallicus and Levant sparrowhawk Accipiter brevipes) as well as storks, pelicans and cranes. Protected mammals were also posted as trophies, including the Near Threatened striped hyaena Hyaena hyaena. Poachers were present in 44% of photographs and were clearly identifiable 89% of the time, showing little concern about posting illegal activities on publicly accessible social media platforms. Our study is the first to use social media as a tool for assessing illegal hunting activities in Lebanon. We discuss both the use and limitations of this approach, as well as the ways in which social media can be utilized by law enforcement, to promote legal hunting or hunting alternatives and improve conservation education.